Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric device
By adjusting the chemical composition of sodium iron pyrophosphate-based positive electrode active materials, the problems of slow Na+ ion diffusion rate and low compaction density were solved, and battery performance was improved.
Patent Information
- Application Number
- CN202410494573.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2025-10-24
AI Technical Summary
The Na+ ion diffusion rate of the existing sodium iron phosphate pyrophosphate positive electrode active material is slow, and the compaction density of the formed active material layer is low.
By controlling the chemical composition of the positive electrode active material NaxRyPmOn, it is made to be in a phosphorus-deficient state, promoting the lattice to grow along the (602) crystal plane orientation to shorten the Na+ transmission path, and making the small particles flat, thereby increasing the Na+ diffusion rate and the compaction density of the active material layer.
The battery's rate performance and first coulombic efficiency are improved, while the compaction density of the active material layer is increased, thereby enhancing the overall performance of the battery.
Smart Images

Figure CN120834150A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery, and an electrical device. Background Art
[0002] Sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7) cathode active materials have the advantages of low cost, environmental friendliness, high theoretical capacity (129mAh / g), high average working voltage (3.1vs.Na + / Na) and low volume expansion (less than 4%), it is considered to be the most promising positive electrode material for sodium ion batteries. However, the Na4Fe3(PO4)2P2O7 prepared so far is + The ion diffusion rate is slow, and the active material layer formed therefrom has a low compaction density. Summary of the Invention
[0003] In view of the above problems, the present application provides a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device, which can improve the Na x R y P m O n Na + The ion diffusion rate can be increased and the compaction density of the active material layer formed therefrom can be improved.
[0004] In a first aspect, the present application provides a positive electrode active material, wherein the positive electrode active material comprises Na x R y P m O n , wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7<m<4, 14.5≤n≤15.5, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, In, Ga, Sn, Hf, Ta, W and Pb.
[0005] In the technical solution of the embodiment of the present application, by making the positive electrode active material Na x R y P m O n 3.7<m<4, positive electrode active material Na x R y P m O n The phosphorus-deficient state is conducive to the growth of the lattice along the (602) crystal plane, shortening the Na + transmission path, improve Na +diffusion rate, and thus is beneficial to the rate performance and the first coulombic efficiency of the battery. At the same time, the small particles of the positive active material Na x R y P m O n present a relatively flat state, which is beneficial to improve the density of the large particles formed by agglomeration, and thus improve the compaction density of the active material layer formed.
[0006] In some embodiments, 3.8≤m<4.
[0007] In the above implementation process, by making the positive active material Na x R y P m O n 3.8≤m<4, on the one hand, the positive active material has a good gram capacity. On the other hand, it is also more beneficial to the lattice growth along the (602) crystal face to shorten the transmission path of Na + , so that the battery using the positive active material has better rate performance and first coulombic efficiency. At the same time, the small particles of the positive active material Na x R y P 4-a O n present a relatively flat state, which is beneficial to improve the density of the large particles formed by agglomeration, and thus improve the compaction density of the active material layer formed.
[0008] In some embodiments, the number of phosphorus vacancies is denoted as a, and the positive active material includes Na x R y P 4-a O n , 0<a<0.3.
[0009] In the above implementation process, by forming phosphorus vacancies in the positive active material Na x R y P 4-a O n , it is beneficial to the lattice growth along the (602) crystal face to shorten the transmission path of Na + , improve the diffusion rate of Na + , and thus is beneficial to the rate performance and the first coulombic efficiency of the battery. At the same time, the small particles of the positive active material Na x R y P 4-a O n present a relatively flat state, which is beneficial to improve the density of the large particles formed by agglomeration, and thus improve the compaction density of the active material layer formed.
[0010] In some embodiments, 0<a≤0.2.
[0011] In the above implementation process, by controlling 0<a≤0.2, it is more beneficial to the lattice growth along the (602) crystal face to shorten the transmission path of Na +The transmission path of the small particles is improved, so that the battery using the positive active material has better rate performance and first coulomb efficiency. Meanwhile, the small particles are in a relatively flat state, which is beneficial to improve the density of the large particles formed by the agglomeration, and thus the active material layer formed by the positive active material has a higher compaction density. In addition, the positive active material also has a good gram capacity.
[0012] In some embodiments, the chemical formula of the positive active material is Na x Fe y P m O n , wherein 3.9≤x≤4.2, 2.8≤y≤3.1, 3.8≤m<4, 14.5≤n≤15.5.
[0013] In some embodiments, the relationship between the X-ray diffraction intensity I(602) of the (602) crystal plane of the positive active material (602) and the X-ray diffraction intensity I(022) of the (022) crystal plane satisfies: I(602) / I(022)=1.12~1.15.
[0014] In the above embodiments, the ratio of the X-ray diffraction intensity I(602) of the (602) crystal plane of the positive active material (602) to the X-ray diffraction intensity I(022) of the (022) crystal plane is 1.12~1.15, which is beneficial to improve the diffusion rate of Na + , and thus is beneficial to the rate performance and first coulomb efficiency of the battery. At the same time, the flatness of the small particles of the positive active material Na x R y P m O n is in a better range, which is beneficial to reduce the pores in the large particles formed by the agglomeration, and at the same time makes the large particles formed by the agglomeration relatively round and have a good sphericity, and thus can better improve the compaction density of the active material layer formed by the positive active material.
[0015] In some embodiments, the relationship between the X-ray diffraction intensity I(602) of the (602) crystal plane of the positive active material (602) and the X-ray diffraction intensity I(022) of the (022) crystal plane satisfies: I(602) / I(022)=1.13~1.14.
[0016] In some embodiments, the porosity of the positive active material is 0.012~0.078cm 3 / g.
[0017] In the above process, by controlling the porosity of the positive active material to be 0.012~0.078cm 3 / g, the compaction density of the active material layer formed by the positive active material is improved.
[0018] In some embodiments, the median particle size Dv50 of the positive electrode active material is 2-3 μm.
[0019] In the above implementation process, the smaller the particle size of the positive electrode active material, the more conducive to the compaction density of the positive electrode active material layer, and thus the more conducive to the volumetric energy density of the battery; and the larger the particle size of the positive electrode active material, the lower the difficulty in its preparation, and the more conducive to the control of its cost. By controlling the median particle size Dv50 of the positive electrode active material to be 2-3 μm, the volumetric energy density of the battery and the control of the cost can be taken into account.
[0020] In some embodiments, the chemical formula of the positive electrode active material is Na x R y P m O n / C, wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7
[0021] In the above implementation process, by compounding the positive electrode active material Na x R y P m O n and C, the positive electrode active material Na x R y P m O n is reduced, and thus the generation of residual alkali in the preparation and use process is reduced.
[0022] In some embodiments, R is denoted as z, and the positive electrode active material includes Na x R 3-z P m O n , 0≤z≤0.5.
[0023] In the above implementation process, by controlling 0≤z≤0.5, the content of the impurities such as NaFePO4 in the positive electrode active material is reduced, and thus the content of Na4R3(PO4)2P2O7 is increased, which is conducive to improving the gram capacity of the positive electrode active material.
[0024] In some embodiments, 0
[0025] In the above implementation process, by controlling 0 < z ≤ 0.2, further reduction of the content of impurities such as NaFePO4 in the positive electrode active material, and further increase of the content of Na4R3(PO4)2P2O7, are conducive to increasing the gram capacity of the positive electrode active material.
[0026] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:
[0027] (a) the first coulombic efficiency of the positive electrode active material is ≥ 93%;
[0028] (b) the gram capacity of the positive electrode active material is 110-126 mAh / g;
[0029] (c) the mass content of residual alkali in the positive electrode active material is ≤ 0.36%.
[0030] In some embodiments, the positive electrode active material satisfies one or more of the following characteristics:
[0031] (a) the first coulombic efficiency of the positive electrode active material is ≥ 94%;
[0032] (b) the gram capacity of the positive electrode active material is 123.2-125.8 mAh / g.
[0033] In some embodiments, the compaction density of the positive electrode sheet is 2.15-2.25 g / cm 3 .
[0034] In a second aspect, the application provides a preparation method of a positive electrode active material, the method comprising:
[0035] mixing a sodium source, an R source and a phosphorus source to obtain a mixture, the molar ratio of Na, R and P in the mixture being 3.5-4.7: 2.3-3.5: 3.5-4, wherein R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, In, Ga, Sn, Hf, Ta, W and Pb;
[0036] sintering the mixture to obtain a positive electrode active material, the positive electrode active material comprising Na x R y P m O n , wherein 3.5 ≤ x ≤ 4.5, 2.5 ≤ y ≤ 3.5, 3.7 < m < 4, 14.5 ≤ n ≤ 15.5.
[0037] In the technical solution of the embodiments of the application, by reducing the addition of the phosphorus source during preparation, the proportion of phosphorus is less than the theoretical value 4, and further the content of Na xR y P m O n The phosphorus-deficient state is conducive to the growth of the lattice along the (602) crystal plane, shortening the Na + transmission path, improve Na + The diffusion rate is improved, which is beneficial to the rate performance and first coulombic efficiency of the battery. At the same time, it also makes the positive electrode active material Na x R y P m O n The small particles are in a relatively flat state, which is beneficial to increasing the density of large particles formed by their agglomeration, and then improving the compaction density of the formed active material layer.
[0038] In some embodiments, the mixture further includes a carbon source.
[0039] In some embodiments, the carbon source comprises a first carbon source and a second carbon source, the first carbon source comprises an inorganic carbon source, and the second carbon source comprises an organic carbon source.
[0040] In the above implementation process, by simultaneously using an inorganic carbon source and an organic carbon source to achieve coating, the crystal growth of the positive electrode active material is facilitated, making the lattice more regular. At the same time, the content of the impurity phase in the positive electrode active material can be reduced, and the gram capacity of the positive electrode active material can be increased. In addition, the positive electrode active material can be well coated, reducing the possibility of Na4R3(PO4)2P2O7 in the positive electrode active material reacting with water in the environment, which is beneficial to the cycle stability of the positive electrode active material.
[0041] In some embodiments, the first carbon source comprises at least one of graphite, carbon black, carbon nanotubes, and graphene; and / or
[0042] The second carbon source includes at least one of sucrose, glucose, citric acid, starch, cyclodextrin, asphalt and PEG.
[0043] In a third aspect, the present application provides a positive electrode plate, which includes a positive electrode active material layer, and the positive electrode active material layer includes the positive electrode active material provided in the first aspect or the positive electrode active material prepared by the method provided in the second aspect.
[0044] In a fourth aspect, the present application provides a battery, which includes the positive electrode plate provided in the third aspect.
[0045] In a fifth aspect, the present application provides an electrical device, which includes the battery provided in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Various other advantages and benefits will become apparent to those of ordinary skill in the art upon reading the following detailed description of the preferred embodiments with reference made to the accompanying drawings. The drawings are for purposes of illustration only and are not intended to limit the scope of the present application. The same reference numbers in different drawings identify the same components throughout the text. In the drawings:
[0047] Figure 1 Structural schematic diagram of a vehicle provided for some embodiments of the present application;
[0048] Figure 2 Exploded structural schematic diagram of a secondary battery provided for some embodiments of the present application;
[0049] Figure 3 Structural schematic diagram of a battery cell provided for some embodiments of the present application;
[0050] Figure 4 Exploded diagram of a battery cell provided for some embodiments of the present application;
[0051] Figure 5 Scanning electron microscope image of a positive electrode active material provided for some embodiments of the present application;
[0052] Figure 6 Flowchart of a preparation method of a positive electrode active material provided for some embodiments of the present application;
[0053] Figure 7 First structural schematic diagram of a positive electrode tab provided for some embodiments of the present application;
[0054] Figure 8 Second structural schematic diagram of a positive electrode tab provided for some embodiments of the present application;
[0055] Figure 9 Preparation flowchart of a battery cell provided for some embodiments of the present application;
[0056] Figure 10 Scanning electron microscope image of a positive electrode active material provided for Comparative Example 2 of the present application;
[0057] Figure 11 Scanning electron microscope image of a positive electrode active material provided for Comparative Example 3 of the present application;
[0058] Figure 12 Scanning electron microscope image of a positive electrode active material provided for Example 3 of the present application.
[0059] Reference signs in the detailed description of the embodiments are as follows:
[0060] 1000 - vehicle; 100 - secondary battery; 200 - motor; 300 - controller; 10 - case; 11 - accommodation space; 12 - first portion; 13 - second portion; 20 - battery cell; 21 - case; 211 - opening; 22 - end cap assembly; 221 - end cap; 222 - electrode terminal; 23 - electrode assembly; 231 - positive electrode tab; 2311 - positive electrode current collector; 2312 - positive electrode active material layer; 24 - current collecting member; 25 - insulation protector. DETAILED DESCRIPTION
[0061] The embodiments of the technical solutions of the present application will be described in detail below with reference to the drawings. The following embodiments are only used to more clearly illustrate the technical solutions of the present application, and therefore only serve as examples, and cannot limit the protection scope of the present application.
[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application; the terms "comprising" and "having," and any variations thereof, as used in the specification and claims and the aforementioned drawings, are intended to cover not only the inclusive but also the exclusive.
[0063] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "a plurality of" is two or more, unless otherwise explicitly and specifically limited.
[0064] Reference herein to "an embodiment" means that a particular feature, structure, or characteristic described in connection with the embodiment can be included in at least one embodiment of the application. The appearance of the phrase in various places in the specification does not necessarily all refer to the same embodiment, nor is it necessarily independent or alternative embodiments to each other. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0065] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, which means that there can be three relationships, for example, A and / or B, which can represent the three cases of A alone, A and B together, and B alone. In addition, the character " / " in this paper generally represents that the front and rear associated objects are a "or" relationship.
[0066] In the description of the embodiments of the present application, the term "a plurality of" refers to two or more (including two), and similarly, "a plurality of groups" refers to two or more groups (including two groups), and "a plurality of pieces" refers to two or more pieces (including two pieces).
[0067] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "transverse", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a particular orientation, be constructed and operated in a particular orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.
[0068] In the description of the embodiments of the present application, unless otherwise explicitly specified and limited, the technical terms "mounting", "connection", "connection", "fixing" and the like should be understood broadly, for example, it can be fixedly connected, or it can be detachably connected, or it can be integrated; it can be mechanically connected, or it can be electrically connected; it can be directly connected, or it can be indirectly connected through an intermediate medium; it can be the internal communication of two elements or the interaction relationship between two elements. For those skilled in the art, the specific meaning of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0069] At present, from the development of market situation, the application of power battery is more and more extensive. Power battery is not only applied to energy storage power supply system such as hydroelectric, thermal, wind and solar power station, but also widely used in electric bicycles, electric motorcycles, electric vehicles and other electric vehicles, military equipment, aerospace and other fields. With the continuous expansion of the application field of power battery, the demand of its market is also increasing.
[0070] The power battery can be a sodium ion battery. The reserves of sodium element are relatively rich, which can significantly reduce the cost of the battery, so the sodium ion battery has broad application prospects, for example, the sodium ion battery can be applied in the field of portable electronic devices, electric vehicles, etc. Sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2P2O7) type positive active material has the characteristics of low cost, environmental friendliness, high theoretical capacity (129 mAh / g), high average working voltage (3.1 V vs. Na + / Na) and low volume expansion (less than 4%), and is considered to be the most potential positive material of sodium ion battery. However, the Na + ion diffusion rate of the prepared Na4Fe3(PO4)2P2O7 is slow, and the compaction density of the active material layer formed thereby is low.
[0071] Based on the above considerations, in order to increase the Na + ion diffusion rate, and improve the compaction density of the active material layer formed therefrom, the present application proposes a positive electrode active material, the positive electrode active material comprising Na x R y P m O n , wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7<m<4, 14.5≤n≤15.5, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, In, Ga, Sn, Hf, Ta, W and Pb.
[0072] In such a positive electrode active material, by making the positive electrode active material Na x R y P m O n 3.7<m<4, which can be used in the positive electrode active material Na x R y P m O n The phosphorus-deficient state is conducive to the growth of the lattice along the (602) crystal plane, shortening the Na + transmission path, improve Na + The diffusion rate is improved, which is beneficial to the rate performance and first coulombic efficiency of the battery. At the same time, it also makes the positive electrode active material Na x R y P m O n The small particles are in a relatively flat state, which is conducive to increasing the density of the large particles formed by their agglomeration, thereby making the active material layer formed therein have a higher compaction density.
[0073] The positive electrode active material can be used to prepare the positive electrode active material layer of a positive electrode sheet, which can be used to prepare an electrode assembly. The electrode assembly can be used, but is not limited to, in electrical devices such as vehicles, ships, or aircraft. The power supply system of the electrical device can be composed of a battery or the like disclosed in this application.
[0074] The present invention provides an electric device that uses a battery as a power source. The electric device may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery-powered vehicle, an electric car, a ship, a spacecraft, etc. The electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc. The spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0075] The following embodiments are described by taking a vehicle 1000 as an example.
[0076] Please refer to Figure 1 , Figure 1 A structural schematic diagram of the vehicle 1000 is provided for some embodiments of the present application. The vehicle 1000 can be a fuel automobile, a gas automobile, or a new energy automobile, which can be a pure electric vehicle, a hybrid electric vehicle, or a range extended vehicle, etc. The vehicle 1000 is internally provided with a secondary battery 100, which can be arranged at the bottom, head or tail of the vehicle 1000. The secondary battery 100 can be used for power supply of the vehicle 1000, for example, the secondary battery 100 can be used as an operating power supply of the vehicle 1000. The vehicle 1000 can further include a controller 300 and a motor 200, and the controller 300 is used to control the secondary battery 100 to supply power to the motor 200, for example, to meet the power demand of the vehicle 1000 during starting, navigation and driving.
[0077] In some embodiments of the present application, the secondary battery 100 can not only be used as an operating power supply of the vehicle 1000, but also be used as a driving power supply of the vehicle 1000, instead of or partially instead of fuel or natural gas to provide driving power for the vehicle 1000.
[0078] In the present application, the secondary battery 100 can refer to a single battery cell 20, which can also refer to a single physical module including a plurality of battery cells 20 to provide higher voltage and capacity, which can be in the form of a battery pack, a battery module, etc. The secondary battery 100 can include a box 10 for packaging a plurality of battery cells 20, and the box 10 can avoid the influence of liquid or other foreign matters on the charging or discharging of the battery cells 20.
[0079] Figure 2 A disassembled structural schematic diagram of the secondary battery 100 is provided for some embodiments of the present application. Please refer to Figure 2 , the secondary battery 100 includes a box 10 and a battery cell 20, and the battery cell 20 is accommodated in the box 10.
[0080] The box 10 is used to provide an accommodation space 11 for the battery cell 20. In some embodiments, the box 10 can include a first part 12 and a second part 13, and the first part 12 and the second part 13 are overlapped with each other to define the accommodation space 11 for accommodating the battery cell 20. Of course, the connection between the first part 12 and the second part 13 can be sealed by a sealing member (not shown in the figure), which can be a sealing ring, sealing glue, etc.
[0081] The first part 12 and the second part 13 can be in various shapes, such as a cuboid, a cylinder, etc. The first part 12 can be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the second part 13 can also be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the open side of the second part 13 is covered on the open side of the first part 12 to form the case 10 with the receiving space 11. Of course, as shown in Figure 2 the first part 12 can be a hollow structure with one side open, the second part 13 can be a plate-shaped structure, and the second part 13 is covered on the open side of the first part 12 to form the case 10 with the receiving space 11.
[0082] In the secondary battery 100, the battery cell 20 is multiple, and the multiple battery cells 20 can be connected in series, in parallel, or in a mixed connection. The mixed connection means that the multiple battery cells 20 are connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in a mixed connection, and then the whole of the multiple battery cells 20 is received in the case 10. Of course, the multiple battery cells 20 can be first connected in series, in parallel, or in a mixed connection to form a battery module, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and are received in the case 10. The battery cell 20 can be in a cylindrical shape, a flat shape, a cuboid shape, or other shapes. Figure 2 An example is shown in which the battery cell 20 is in a square shape.
[0083] In some embodiments, the secondary battery 100 can further include a busbar component (not shown in the figure), and the multiple battery cells 20 can be electrically connected through the busbar component to achieve series connection, parallel connection, or mixed connection of the multiple battery cells 20.
[0084] Figure 3 A structural schematic diagram of the battery cell 20 provided for some embodiments of the present application is shown in Figure 4 An exploded view of the battery cell 20 provided for some embodiments of the present application is shown in Figure 3 and Figure 4 The battery cell 20 can include a shell 21, an end cap assembly 22, and an electrode assembly 23. The shell 21 has an opening 211, the electrode assembly 23 is received in the shell 21, and the end cap assembly 22 is used to cover the opening 211.
[0085] The shape of the shell 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is in a cuboid structure, the shell 21 can also be in a cuboid structure. Figure 3 and Figure 4 An example is shown in which the shell 21 and the electrode assembly 23 are in a square shape.
[0086] The shell 21 may be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0087] The end cap assembly 22 includes an end cap 221 and an electrode terminal 222. The end cap assembly 22 is used to seal the opening 211 of the outer shell 21 to form a sealed installation space (not shown), which is used to accommodate the electrode assembly 23. The installation space is also used to accommodate an electrolyte, such as an electrolyte. The end cap assembly 22 serves as a component for outputting the electrical energy of the electrode assembly 23. The electrode terminal 222 in the end cap assembly 22 is used to electrically connect to the electrode assembly 23, that is, the electrode terminal 222 is electrically connected to the tab of the electrode assembly 23. For example, the electrode terminal 222 is connected to the tab through the current collecting member 24 to achieve electrical connection between the electrode terminal 222 and the tab.
[0088] It should be noted that the number of openings 211 of the outer shell 21 can be one or two. If the number of openings 211 of the outer shell 21 is one, the number of end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22. The two electrode terminals 222 are respectively used to electrically connect to the positive electrode tab and the negative electrode tab of the electrode assembly 23. If the number of openings 211 of the outer shell 21 is two, for example, the two openings 211 are provided on opposite sides of the outer shell 21, the number of end cap assemblies 22 can also be two, and the two end cap assemblies 22 are respectively covered on the two openings 211 of the outer shell 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal 222, which is used to electrically connect to the positive electrode tab of the electrode assembly 23; and the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal 222, which is used to electrically connect to the negative electrode sheet of the electrode assembly 23.
[0089] In some embodiments, as Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the periphery of the electrode assembly 23. The insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the outer casing 21. Exemplarily, the insulating protective member 25 is a tape adhered to the periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 is disposed around the periphery of the multiple electrode assemblies 23, forming the multiple electrode assemblies 23 into a single integral structure to maintain the structural stability of the electrode assemblies 23.
[0090] The electrode assembly 23 includes a positive electrode sheet 231, a negative electrode sheet, and a separator. The separator is located between the positive electrode sheet 231 and the negative electrode sheet to provide insulation. The electrode assembly 23 can be a wound or laminated structure, but the present invention is not limited thereto.
[0091] This application has no particular restrictions on the positive electrode sheet 231 , the negative electrode sheet, and the separator.
[0092] In some embodiments, the separation film can be a PP (polypropylene) porous film, a PE (polyethylene) porous film, a polyimide porous film, and a porous film formed by a plurality of polymers, etc.
[0093] In some embodiments, the positive electrode tab 231 includes a positive electrode current collector 2311 and a positive electrode active material layer 2312 covering at least one surface of the positive electrode current collector 2311 in the thickness direction; the positive electrode current collector 2311 without the positive electrode active material layer 2312 protrudes from the positive electrode current collector 2311 with the positive electrode active material layer 2312, and the positive electrode current collector 2311 without the positive electrode active material layer 2312 serves as a positive electrode tab. The material of the positive electrode current collector 2311 can include an aluminum foil, a foamed aluminum, an aluminum composite current collector (a current collector with a polymer support layer in the middle, and aluminum metal layers on both surfaces of the support layer), a nickel foil, a foamed nickel, etc.; the positive electrode active material in the positive electrode active material layer 2312 includes one or a mixture of several of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-containing olivine phosphate, for example, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, etc.; the binder in the positive electrode active material layer 2312 is selected from at least one of vinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylate, carboxymethyl cellulose sodium salt, butadiene-styrene rubber, polyurethane, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid copolymer; the dispersant in the positive electrode active material layer 2312 is selected from polyvinylpyrrolidone, etc.; and the conductive particles in the positive electrode active material layer 2312 are selected from at least one of conductive carbon black, acetylene black, ketjen black, carbon fiber, carbon nanotube, graphene, activated carbon, graphite sheet, graphite particle, and mesocarbon microbead.
[0094] In some embodiments, the positive electrode tab can be prepared by dispersing the above-mentioned components for preparing the positive electrode tab 231, such as the positive electrode active material, the conductive agent, the binder, and any other components, in a solvent (for example, N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry on the positive electrode current collector, and after drying, cold pressing, etc., the positive electrode tab can be obtained.
[0095] In some embodiments, the negative electrode tab includes a negative electrode current collector and a negative electrode active material layer covering at least one surface of the negative electrode current collector in the thickness direction; the negative electrode current collector not coated with the negative electrode active material layer protrudes from the negative electrode current collector coated with the negative electrode active material layer, and the negative electrode current collector not coated with the negative electrode active material layer serves as a negative electrode tab. The material of the negative electrode current collector can include a copper foil, a copper alloy foil, a nickel foil, a stainless steel foil, a titanium foil, a foamed nickel, a foamed copper, or a polymer substrate coated with a conductive metal, wherein the conductive metal includes but is not limited to copper, nickel, or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate, and poly-p-phenylene terephthalamide; the negative electrode active material in the negative electrode active material layer includes a carbon material, lithium element, or an alloy of lithium and other metal elements or non-metal elements, wherein the carbon material includes but is not limited to at least one of hard carbon, soft carbon, amorphous carbon, nanostructured carbon material, etc., and all of these materials can be obtained through commercial channels. The metal elements include tin (Sn), zinc (Zn), aluminum (Al), magnesium (Mg), silver (Ag), gold (Au), gallium (Ga), indium (In), platinum (Pt), etc., and the non-metal elements include boron (B), carbon (C), silicon (Si), etc.
[0096] In other embodiments, the current collector of the negative electrode tab can generally further include a current collector body and a primer layer, the primer layer can be provided on at least one side of the current collector body, the primer layer is substantially free of negative electrode active material and can include a small amount of carbon material, but the carbon material forms a coating layer with a thickness that is too thin to function as negative electrode active material. In this embodiment, the negative electrode tab can be a tab without a negative electrode active material layer. For the negative electrode tab without a negative electrode active material layer, when the current collector of the negative electrode tab is free of a primer layer, the film layer of the negative electrode tab can be provided on the surface of at least one side of the current collector body; when the current collector of the negative electrode tab includes a primer layer, the film layer of the negative electrode tab can be provided on the surface of the side of the primer layer away from the current collector body.
[0097] In some embodiments, the electrolyte functions to conduct ions between the positive electrode tab and the negative electrode tab. The type of electrolyte is not specifically limited in the present application and can be selected as needed. For example, the electrolyte can be liquid, gel, or all-solid.
[0098] In some embodiments, the electrolyte uses an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0099] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonylimide, lithium bis-trifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorobisoxalate borate, lithium bisoxalate borate, lithium difluorobisoxalate phosphate, and lithium tetrafluorobisoxalate phosphate.
[0100] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, methyl ethyl sulfone, and diethyl sulfone.
[0101] In some embodiments, the electrolyte can further optionally include an additive. For example, the additive can include a negative electrode film-forming additive, a positive electrode film-forming additive, and can further include an additive capable of improving certain performance of the battery, such as an additive for improving overcharge performance of the battery, an additive for improving high-temperature or low-temperature performance of the battery, etc.
[0102] Figure 5 A scanning electron microscope image of the positive electrode active material provided by some embodiments of the present application is shown in FIG. 1. Figure 5 The positive electrode active material provided by some embodiments of the present application includes Na x R y P m O n wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7
[0103] The content of each element can be obtained by inductively coupled plasma emission spectrometry (ICP).
[0104] By setting 3.7 x R y P m O n to 4, the positive electrode active material Na x R y P m O n exhibits a lack of phosphorus state, which is conducive to the growth of the lattice of the positive electrode active material Na + along the (602) crystal plane, shortens the transmission path of Na + , and improves the diffusion rate of Na + , thereby being conducive to the rate performance and the initial coulombic efficiency of the battery. At the same time, the positive electrode active material Na x R y P m O nThe small particles are in a relatively flat state, which is conducive to increasing the density of the large particles formed by agglomeration, and thus the active material layer formed thereby has a higher compaction density.
[0105] It should be noted that the above limitation of x includes the molar content of Na under different charge-discharge states of the battery (usually the battery voltage is between 2-5V).
[0106] Understandably, the battery will be accompanied by sodium (Na) deintercalation and consumption during charging and discharging, and the content of Na in the positive plate will be different when the battery is discharged to different states. Among them, the content of Na can be measured by molar content, but not limited to this. At the same time, the positive plate applied to the battery system by the positive material will change the content of Na in the positive material contained in the plate after charging and discharging cycle. In this application, the content of Na in the listed positive material is the initial state of the material, unless otherwise stated. Regarding "the content of Na is the initial state of the material", the initial state of the material refers to the state before being put into the positive slurry. It can be understood that the new material obtained by properly modifying the listed positive material is also within the scope of the positive material, and the foregoing proper modification refers to acceptable modification methods for the positive material, and non-limiting examples include coating modification.
[0107] It can be understood that the molar content of R y and the molar content of Na have similar situations, which are not described here.
[0108] For example, Na x R y P m O n In x can be 3.5, 3.55, 3.6, 3.65, 3.7, 3.75, 3.8, 3.85, 3.9, 3.95, 4, 4.05, 4.1, 4.15, 4.2, 4.25, 4.3, 4.35, 4.4, 4.45 or 4.5, etc. It can also be any value in the range of 3.5-4.5. Na x R y P m O n In y can be 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4 or 3.5, etc. It can also be any value in the range of 2.5-3.5. Na x R y P m O n In m can be 3.7, 3.75, 3.8, 3.85, 3.9, 3.91, 3.92, 3.93, 3.94, 3.94, 3.95, 3.96, 3.97, 3.98, or 3.99, etc. It can also be any value in the range of 3.7-4. Na x Ry P m O n n can be 14.5, 14.6, 14.7, 14.8, 14.9, 15, 15.1, 15.2, 15.3, 15.4 or 15.5, etc., which can also be any value in the range of 14.5-15.5.
[0109] In the technical solution of some embodiments of the present application, 3.8≤m<4. By making the positive electrode active material Na x R y P m O n 3.8≤m<4, on the one hand, the positive electrode active material has a good specific capacity. On the other hand, it is also more conducive to the lattice along the (602) crystal face orientation growth of Na + shortening the transmission path, so that the battery using the positive electrode active material has better rate performance and first coulomb efficiency. At the same time, the small particles present a relatively flat state, which is conducive to improving the density of the large particles formed by agglomeration, and thus the active material layer formed by it has a higher compaction density.
[0110] In the technical solution of some embodiments of the present application, the number of phosphorus vacancies is denoted as a, and the positive electrode active material includes Na x R y P 4-a O n , 0<a<0.3.
[0111] Vacancies are a kind of point defects, and point defects are a kind of crystal defects, which are a defect that deviates from the normal arrangement of the crystal structure at the junction or in the adjacent micro area. Point defects occur within one or several lattice constants in the crystal, and their sizes in three-dimensional directions are very small. The number of vacancies refers to the difference between the theoretical number and the actual number of a certain element in the crystal lattice. The number of phosphorus vacancies a refers to the difference between the theoretical number 4 and the actual number of phosphorus elements in the crystal lattice. For example, the content of each element in the entire positive electrode active material can be obtained by inductively coupled plasma emission spectrometry (ICP), and the content of the impurity phase in the positive electrode active material can be detected, the content of each element in the impurity phase (such as NaRPO4) can be calculated according to the chemical formula and content of the impurity phase, and the content of each element in the positive electrode active material can be obtained by subtracting the content of each element in the impurity phase (such as NaRPO4) from the content of each element in the entire positive electrode active material to obtain the chemical formula of Na x R y P 4-a O n , and then the number of phosphorus vacancies a is obtained. The detection of the impurity phase and its content can be performed by XRD and other methods.
[0112] By making the positive electrode active material Na x R y P4-a O n The phosphorus vacancies are formed in the middle, which is beneficial to the lattice along the (602) crystal face orientation growth shortening the transmission path of Na + , improving the diffusion rate of Na + , and further improving the rate performance and the initial coulomb efficiency of the battery. At the same time, the small particles of the positive active material Na x R y P 4-a O n present a relatively flat state, which is beneficial to improving the density of the large particles formed by agglomeration, and further improving the compaction density of the active material layer formed.
[0113] In the technical scheme of some embodiments of the present application, 0 + The transmission path of Na x R y P m O n is shortened, so that the battery using the positive active material has better rate performance and initial coulomb efficiency. At the same time, the small particles of the positive active material Na x Fe y P m O n present a relatively flat state, which is beneficial to improving the density of the large particles formed by agglomeration, and further improving the compaction density of the active material layer formed.
[0114] In the technical scheme of some embodiments of the present application, the chemical formula of the positive active material is Na x Fe y P m O n , wherein 3.9
[0115] In the technical scheme of some embodiments of the present application, the relationship between the X-ray diffraction intensity I(602) of the (602) crystal face of the positive active material and the X-ray diffraction intensity I(022) of the (022) crystal face satisfies: I(602) / I(022)=1.12-1.15. The ratio of the X-ray diffraction intensity I(602) of the (602) crystal face of the positive active material and the X-ray diffraction intensity I(022) of the (022) crystal face is 1.12-1.15, which is beneficial to improving the diffusion rate of Na + , and further improving the rate performance and the initial coulomb efficiency of the battery. At the same time, the small particles of the positive active material Na x R y P m O nThe flatness of the small particles is in a preferable range, which is conducive to reducing the pores in the large particles formed by the agglomeration of the small particles, while keeping the large particles formed by the agglomeration of the small particles relatively round and having good sphericity, thereby being able to better improve the compaction density of the active material layer formed by the active material.
[0116] For example, the ratio of the X-ray diffraction intensity I(602) of the crystal face of the positive electrode active material (602) to the X-ray diffraction intensity I(022) of the crystal face (022) can be 1.12, 1.13, 1.14 or 1.15, etc., and can also be any value in the range of 1.12-1.15.
[0117] In the technical scheme of some embodiments of the present application, the relationship between the X-ray diffraction intensity I(602) of the crystal face of the positive electrode active material (602) and the X-ray diffraction intensity I(022) of the crystal face (022) satisfies I(602) / I(022) = 1.13-1.14.
[0118] In the technical scheme of some embodiments of the present application, the porosity of the positive electrode active material is 0.012-0.078 cm 3 / g.
[0119] The porosity refers to the percentage of the nitrogen measurable pore volume in the above-mentioned positive electrode active material to the total volume of the positive electrode active material in a natural state.
[0120] The testing method of the porosity can be as follows: using a specific surface area and porosity tester, placing an accurately weighed pretreated sample in a sample tube, first vacuumizing and degassing, then making the whole system reach the required vacuum degree, then immersing the sample tube in a liquid nitrogen bath and filling nitrogen, the adsorbent adsorbing gas will cause a pressure drop, after reaching the adsorption equilibrium, the equilibrium pressure of the gas is measured, and the adsorption amount can be calculated according to the pressure change of the system before and after adsorption; the pressure is changed by successively increasing the amount of adsorbate gas in the system, and the above-mentioned operation is repeated to test the adsorption and desorption isotherms; and the porosity of the measured sample is calculated by using a theoretical model.
[0121] By controlling the porosity of the positive electrode active material to be 0.012-0.078 cm 3 / g, the compaction density of the active material layer formed by the active material can be improved.
[0122] For example, the porosity of the positive electrode active material can be 0.012 cm 3 / g, 0.02 cm 3 / g, 0.03 cm 3 / g, 0.04 cm 3 / g, 0.05 cm 3 / g, 0.06 cm 3 / g, 0.07 cm3 / g or 0.078 cm 3 / g or 0.012-0.078 cm 3 / g or any value within the range of 0.012-0.078 cm.
[0123] In some embodiments of the technical solutions of the present application, the median particle size Dv50 of the positive electrode active material is 2-3 μm.
[0124] The median particle size Dv50 is the particle size corresponding to 50% of the cumulative amount in the volume particle size cumulative distribution diagram. The volume particle size cumulative distribution diagram, also known as the differential distribution diagram of particle size, is a curve plotted with particle size as the abscissa and the differential distribution of content at different sizes of particle size as the ordinate, which can accurately reflect the particle size distribution characteristics of the material particles. Among them, the volume particle size distribution of the material can be measured by using a laser particle size analyzer, and the interval particle size distribution curve can be plotted. When measuring the median particle size of the positive electrode active material in the active material layer of the electrode sheet, the positive electrode active material layer can be taken down, soaked in a solvent NMP, and the binder in the positive electrode active material layer is washed out to obtain the powder material of the positive electrode active material layer, and the powder material is dried and then detected by using a laser particle size analyzer of model Mastersizer3000 to obtain the volume particle size cumulative distribution diagram. The median particle size of polycrystalline particles and single-crystal particles can be obtained according to the peak in the volume particle size cumulative distribution diagram.
[0125] The median particle size Dv50 of the positive electrode active material refers to that the positive electrode active material is accumulated from small to large, and when accumulated to 50% of the total volume, the particle size of the positive electrode active material at this time is the median particle size Dv50.
[0126] The smaller the particle size of the positive electrode active material, the more conducive to the compaction density of the positive electrode active material layer, and thus the more conducive to the volume energy density of the battery; and the larger the particle size of the positive electrode active material, the lower the difficulty of its preparation, and the more conducive to the control of its cost. By controlling the median particle size Dv50 of the positive electrode active material to be 2-3 μm, the volume energy density of the battery and the control of the cost can be taken into account.
[0127] For example, the median particle size Dv50 of the positive electrode active material can be 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm or 3 μm, etc., which can also be any value within the range of 2-3 μm.
[0128] In some embodiments of the technical solutions of the present application, the chemical formula of the positive electrode active material is Na x R y P m O n / C, wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7
[0129] Na x R y P m O n / C refers to a complex of Na x R y P m O n and C.
[0130] By compounding the positive electrode active material Na x R y P m O n and C, the positive electrode active material Na x R y P m O n is reduced, and the production of residual alkali during preparation and use is reduced.
[0131] In the technical scheme of some embodiments of the present application, the number of R vacancies is denoted as z, and the positive electrode active material comprises Na x R 3- z P m O n , 0≤z≤0.5.
[0132] A vacancy is a kind of point defect, and a point defect is a kind of crystal defect that deviates from the normal arrangement of a crystal structure at a node or in a micro area adjacent to the node. A point defect is a defect that occurs within one or several lattice constants in a crystal, and the size thereof in three-dimensional directions is very small. The number of vacancies refers to the difference between the theoretical number and the actual number of a certain element in a crystal lattice. The number of R vacancies z refers to the difference between the theoretical number 3 and the actual number of R elements in a crystal lattice. For example, the content of each element in the entire positive electrode active material can be obtained by inductively coupled plasma emission spectrometry (ICP), and the impurity phase and its content in the positive electrode active material can be detected, the content of each element in the impurity phase (such as NaRPO4) can be calculated according to the chemical formula and content of the impurity phase, and the number of Na x R 3-z P m O nand then R is obtained. The detection of the impurity phase and its content can be performed by XRD and the like.
[0133] By controlling 0≤z≤0.5, the content of the impurity phase such as NaFePO4 in the positive active material is reduced, and the content of Na4R3(PO4)2P2O7 is increased, which is beneficial to improve the gram capacity of the positive active material.
[0134] In the technical scheme of some embodiments of the present application, 0
[0135] In the technical scheme of some embodiments of the present application, the positive active material satisfies one or more of the following characteristics:
[0136] (a) the first coulombic efficiency of the positive active material is ≥93%;
[0137] (b) the gram capacity of the positive active material is 110-126 mAh / g;
[0138] (c) the mass content of residual alkali in the positive active material is ≤0.36%.
[0139] For example, the first coulombic efficiency of the positive active material can be 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.1%, 99.2%, 99.3%, 99.4%, or 99.5%, etc., and it can also be any value within the range of >92.6%. The gram capacity of the positive active material can be 110 mAh / g, 112 mAh / g, 115 mAh / g, 118 mAh / g, 121 mAh / g, 124 mAh / g, or 126 mAh / g, etc., and it can also be any value within the range of 110-126 mAh / g. The mass content of residual alkali in the positive active material can be 0, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, or 0.36%, etc., and it can also be any value within the range of ≤0.36%.
[0140] In the technical scheme of some embodiments of the present application, the positive active material satisfies one or more of the following characteristics:
[0141] (a) the first coulombic efficiency of the positive active material is ≥94%;
[0142] (b) the gram capacity of the positive active material is 123.2-125.8 mAh / g.
[0143] For example, the first coulombic efficiency of the positive active material can be 94%, 95%, 96%, 97%, 98%, 99%, 99.1%, 99.2%, 99.3%, 99.4%, or 99.5%, etc., and it can also be any value within the range of >92.6%. The gram capacity of the positive active material can be 123.2 mAh / g, 124.2 mAh / g, 125.2 mAh / g, or 125.8 mAh / g, etc., and it can also be any value within the range of 123.2-125.8 mAh / g.Figure 6 The flow chart of the preparation method of the positive electrode active material provided in some embodiments of the present application is shown in the following. Figure 6 The present application further provides a preparation method of a positive electrode active material, which comprises the following steps:
[0144] S110. Mixing a sodium source, an R source and a phosphorus source to obtain a mixture, wherein the molar ratio of Na, R and P in the mixture is 3.5-4.7:2.3-3.5:3.5-4, and R comprises at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, In, Ga, Sn, Hf, Ta, W and Pb;
[0145] The sodium source can be at least one of a sodium salt, sodium hydroxide or sodium oxide. The phosphorus source comprises at least one of a phosphate or phosphoric acid. The R source comprises at least one of a salt, an oxide or a hydroxide of the R element, and the R source can be an iron source.
[0146] In the technical solution of some embodiments of the present application, the mixture further comprises a carbon source.
[0147] In the technical solution of some embodiments of the present application, the carbon source comprises a first carbon source and a second carbon source, the first carbon source comprises an inorganic carbon source, and the second carbon source comprises an organic carbon source. By simultaneously using the inorganic carbon source and the organic carbon source to achieve coating, the crystal growth of the positive electrode active material is facilitated, and the regularity of the crystal lattice is higher. At the same time, the content of impurities in the positive electrode active material is reduced, and the specific capacity of the positive electrode active material is improved. In addition, the positive electrode active material can be coated well, the possibility of reaction between Na4R3(PO4)2P2O7 in the positive electrode active material and water in the environment is reduced, and the cycle stability of the positive electrode active material is improved.
[0148] The first carbon source comprises at least one of graphite, carbon black, a carbon nanotube and graphene, and the second carbon source comprises at least one of sucrose, glucose, citric acid, starch, cyclodextrin, pitch and PEG.
[0149] S120. Sintering the mixture to obtain a positive electrode active material, wherein the positive electrode active material comprises Na x R y P m O n , wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7
[0150] It should be noted that, since the phosphorus is consumed in other ways during the preparation process, the amount of phosphorus added is greater than the amount of phosphorus in the final product, i.e., the positive electrode active material Na x R y Pm O n The m in the above formula can be understood as the amount of phosphorus added and the final product positive electrode active material Na x R y P m O n The m in the above formula can be understood as the amount of phosphorus added and the final product positive electrode active material Na
[0151] The method reduces the addition of a phosphorus source during preparation, so that the proportion of phosphorus is less than the theoretical value 4, thereby making the positive electrode active material Na x R y P m O n The m in the above formula can be understood as the amount of phosphorus added and the final product positive electrode active material Na + The m in the above formula can be understood as the amount of phosphorus added and the final product positive electrode active material Na + The m in the above formula can be understood as the amount of phosphorus added and the final product positive electrode active material Na x R y P m O n The m in the above formula can be understood as the amount of phosphorus added and the final product positive electrode active material Na
[0152] Figure 7 A first structural schematic diagram of the positive electrode plate 231 provided by some embodiments of the present application is shown in FIG. 1A. Figure 8 A second structural schematic diagram of the positive electrode plate 231 provided by some embodiments of the present application is shown in FIG. 1B. Figure 7 and Figure 8 The positive electrode plate 231 provided by the embodiments of the present application includes a positive electrode active material layer 2312, and the positive electrode active material layer 2312 includes the positive electrode active material provided above.
[0153] In the technical solution of some embodiments of the present application, the compaction density of the positive electrode plate is 2.15-2.25 g / cm 3 .
[0154] For example, the compaction density of the positive electrode plate can be 2.15 g / cm 3 , 2.16 g / cm 3 , 2.17 g / cm 3 , 2.18 g / cm 3 , 2.19 g / cm 3 , 2.2 g / cm 3 , 2.21 g / cm 3 , 2.22 g / cm 3 , 2.23 g / cm 3 , 2.24 g / cm 3or 2.25g / cm 3 etc., which can also be 2.15 to 2.25 g / cm 3 Any value in the range.
[0155] Please continue reading Figure 7 The positive electrode active material layer 2312 can be provided on one side of the positive electrode current collector. Figure 8 The positive electrode active material layer 2312 may also be provided on both sides of the positive electrode current collector. The material of the positive electrode current collector 2311 may be one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy.
[0156] After the above introduction to the materials and structure of the battery cell 20 , the preparation method of the battery cell 20 will be specifically introduced below.
[0157] The preparation method of the battery cell 20 includes the following steps: mixing the positive electrode active material, the conductive agent and the binder, and then mixing them with a solvent to prepare a positive electrode active slurry, coating the positive electrode active slurry on the positive electrode collector 2311 to obtain the positive electrode plate 231, and after preparing the positive electrode plate 231, the positive electrode plate 231, the isolation membrane, the negative electrode plate, the isolation membrane, and so on, are stacked in sequence to form a laminated electrode assembly 23, and then the electrode assembly 23 is placed in a shell, and the electrolyte is injected to form a battery cell 20.
[0158] Figure 9 The preparation flow chart of the battery cell 20 provided in some embodiments of the present application is as follows: Figure 9 As shown, the specific process of preparing the battery cell 20 is as follows:
[0159] S210, preparing a positive electrode active slurry: dispersing a positive electrode active material, a binder, and a conductive agent in a solvent to form a positive electrode active slurry. The positive electrode active material is the positive electrode active material provided above. A small amount of other positive electrode active materials may optionally be added.
[0160] The binder can be one or more of styrene-butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyvinyl alcohol, and polyvinyl butyral. The conductive agent can be at least one of conductive carbon black, carbon fiber, carbon nanotubes, Ketjen black, graphene, or acetylene black. The solvent can be one or more of dimethyl glutarate and N-methylpyrrolidone. Leveling agents, dispersants, and the like can also be added to the positive electrode active slurry.
[0161] S220, preparing the positive electrode active material layer 2312: coating the positive electrode active paste on the surface of the positive electrode current collector 2311, and then drying to form the positive electrode active material layer 2312. In this process, the coating can be performed on one surface or both surfaces of the positive electrode current collector 2311 according to requirements.
[0162] The coating method can be blade coating, roller coating, slot coating, etc., which are not limited in the present application.
[0163] The positive electrode current collector 2311 can be a metal foil or a composite current collector. For example, as the metal foil, an aluminum foil can be used. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0164] S230, rolling the positive electrode active material layer 2312 to obtain the positive electrode sheet 231.
[0165] S240, stacking the positive electrode sheet 231, the separator film, the negative electrode sheet, the separator film, and so on in sequence to form the laminated electrode assembly 23.
[0166] S250, assembling the laminated electrode assembly 23 into the battery monomer 20. The battery monomer 20 can be used to prepare the secondary battery 100 and provide electric energy for the electric device.
[0167] One or more embodiments will be described in more detail below with reference to the following examples. Of course, these examples do not limit the scope of one or more embodiments.
[0168] Examples and Comparative Examples
[0169]
Preparation of the positive electrode active material
[0170] The sodium source, the R source, and the phosphorus source were dissolved in deionized water in a certain molar ratio, continuously stirred at room temperature for 30 min to obtain an initial mixed slurry. The first carbon source and the second carbon source were dissolved in deionized water to obtain a carbon solution, and the carbon solution and the initial mixed solution were mixed to obtain a mixed solution. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 109°C to obtain a powdery precursor. Finally, the precursor was heated to 320°C at a heating rate of 2°C, and then heated to 550°C at a heating rate of 2°C for 10 h under N2 atmosphere. The sintered product was subjected to airflow crushing and sieving to obtain a positive electrode active material with uniform particle size.
[0171] Preparation of the positive electrode sheet
[0172] 2.5wt% of the binder polyvinylidene fluoride was fully dissolved in the solvent N-methyl pyrrolidone, 2.0wt% of super p and 1.0wt% of CNT were added as conductive agent, and 94.5wt% of the above-mentioned positive active material was made into a uniformly dispersed slurry. The slurry was uniformly coated on the surface of the positive current collector aluminum foil, and then dried, cold-pressed, and cut to obtain the positive electrode sheet.
[0173] Preparation of the negative electrode sheet
[0174] Metallic sodium sheets were used as the negative electrode sheet.
[0175] Preparation of the electrolyte
[0176] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), the organic solvent ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) was mixed uniformly according to the volume ratio of 1 / 1 / 1, 1 mol / L NaPF6 sodium salt was added and uniformly dispersed, and then 5% fluoroethylene carbonate was dissolved in the above-mentioned organic solvent, stirred uniformly, and the electrolyte was obtained.
[0177] Separation film
[0178] A polyethylene film was used as the separation film.
[0179] Preparation of the button cell
[0180] The prepared positive electrode sheet, negative electrode sheet, separation film, and electrolyte were assembled into a CR2430 type button cell in an argon-protected glove box.
[0181] The main parameters of the examples 1 to 16 and the comparative examples 1 to 2 are shown in the following table:
[0182]
[0183]
[0184] In the table, x', y', and m' respectively refer to the molar ratio of the sodium source, the R source, and the phosphorus source.
[0185] " / " indicates that the material is not added or the value does not exist.
[0186] The positive active material provided by each example and comparative example and the battery composed thereof were subjected to performance detection, and the performance detection specifically included:
[0187] Compaction density test: the mass (g / cm2) of the positive active material layer on one side per unit area was measured, and the compaction density was calculated according to the formula: compaction density = mass / area. 2) and the thickness (cm) of the single-sided positive electrode active material layer (number of collection points > 14) are determined. Specifically, the compaction density PD of the positive electrode active material layer = the mass of the single-sided positive electrode active material layer per unit area (g / cm 2 ) / the thickness of the positive electrode active material layer (cm).
[0188] Surface residual alkali mass test: The acid-base titration method is used to titrate sodium bicarbonate and sodium carbonate in the positive electrode material with a hydrochloric acid standard solution, a pH electrode is used as an indicating electrode, and the end point is determined by a sudden change in potential. According to the titration end point, the titration volume of the standard solution is determined. The mass of Na2CO3 and NaHCO3 obtained by calculation is divided by the mass of the positive electrode active material, and the sodium ion mass content is taken as the residual alkali content of the positive electrode active material. The calculation formula is as follows:
[0189] Na2CO3% = (V2-V1)*C*106*100n / 1000m
[0190] NaHCO3% = V2*C*84*n*100 / 1000m
[0191] Na + % = V2*C*23*n*100 / 1000m.
[0192] Gram capacity test: After the battery is left for 12 hours, constant current discharge is carried out at a current of 0.05C until 0.005V, left for 10 minutes. Constant current discharge is carried out again at a current of 50μA until 0.005V, left for 10 minutes. Constant current discharge is carried out again at a current of 10μA until 0.005V. Then constant current charging is carried out at a current of 0.1C until 2V. The charging capacity is recorded. The ratio of the charging capacity to the weight of the positive electrode active material is the gram capacity of the prepared positive electrode active material.
[0193] First coulombic efficiency test: The first coulombic efficiency test process is as follows: at 25°C, the prepared battery is charged to 3.75V at a constant current of 1 / 5C, then charged at a constant voltage of 3.75V until the current drops to 0.05C, to obtain the first charge capacity (Cc1); then discharged to 1.5V at a constant current of 1 / 5C to obtain the first discharge capacity (Cd1), and the battery coulombic efficiency is calculated according to the following formula: battery first coulombic efficiency = first discharge capacity (Cd1) / first charge capacity (Cc1).
[0194] The test results are shown in Table 1 as follows:
[0195]
[0196] From the above table, it can be seen that the positive electrode active material prepared by the method provided in the present application has a smaller porosity, and thus the prepared active material layer has a higher compaction density. Meanwhile, the positive electrode active material has a higher first coulomb efficiency.
[0197] From the comparison of the data of Examples 1 to 2 and Comparative Examples 1 and 3, it can be seen that when the positive electrode active material has a phosphorus deficiency, the porosity of the positive electrode active material is reduced to a certain extent, and the first coulomb efficiency is improved to a certain extent. In the preparation process, as the amount of the phosphorus source added is reduced, i.e. the amount of the phosphorus deficiency of the positive electrode active material is increased, the porosity of the positive electrode active material gradually decreases, the compaction density of the positive electrode active material layer prepared therefrom gradually increases, and the first coulomb efficiency gradually increases, but the specific capacity gradually decreases. When the value of m is less than 4, the positive electrode active material has a smaller porosity, a better specific capacity and a first coulomb efficiency. Further, when the value of m is 3.8 to 4, the flatness of the small particles of the positive electrode active material is in a better range, and the positive electrode active material can form more effective active ingredients, so that the performance of the compaction density, the first coulomb efficiency and the specific capacity can be considered, the porosity of the positive electrode active material is less than 0.028 cm 3 / g, the specific capacity is more than 110.0 mAh / g, and the compaction density of the positive electrode active material layer formed therefrom is more than 2.19 g / cm 3 The first coulomb efficiency of the battery formed above is more than 96.6%.
[0198] From the comparison of the data of Examples 5 to 7, Comparative Example 1 and Comparative Example 2, it can be seen that when the positive electrode active material has an iron defect, the residual alkali content of the positive electrode active material is obviously reduced, and the specific capacity is obviously improved. In the preparation process, as the amount of the iron source added is reduced, i.e. the iron defect of the positive electrode active material is increased, the residual alkali of the positive electrode active material presents a trend of first decreasing and then increasing. When the value of the iron defect y is less than 0.5, the residual alkali of the positive electrode active material is controlled to be less than 0.22%, and further, when the value of the iron defect y is less than 0.2, the residual alkali of the positive electrode active material is controlled to be less than 0.21%, and the porosity of the positive electrode active material is controlled to be less than 0.025 cm 3 / g, and thus the positive electrode active material layer formed therefrom has a better compaction density. It is speculated that the reduction of the residual alkali is beneficial to the control of the porosity, and thus is beneficial to the compaction density.
[0199] From the data of Example 3 and Examples 8 to 9, it can be seen that the selection of different R sources has basically the same effect.
[0200] From the comparison of the data of Example 3 and Examples 10 to 12, it can be seen that the residual alkali content can be well controlled by using different carbon-coated raw materials, and the tap density can also be well maintained. In particular, when two carbon sources are used, the residual alkali content can be better controlled, and the tap density can also be better maintained.
[0201] The scanning electron microscopy test results provided by Example, Comparative Example 2 and Comparative Example 3 are shown in the following table. Figure 10 to 12
[0202] The positive electrode active material of Comparative Example 2 is not deficient in phosphorus, and from Figure 10 it can be seen that the small particles formed thereby are relatively round, and the large particles formed by agglomeration thereof have many pores, and the corresponding material has a relatively low tap density, only 2.12 g / cm 3 .
[0203] The positive electrode active material of Comparative Example 3 is deficient in phosphorus but not in the range of 3.7 < m < 4, and from Figure 11 it can be seen that the flatness of the small particles formed thereby is too high, and the sphericity of the large particles formed by agglomeration thereof is poor, so that the tap density of the positive electrode active material layer formed thereby is relatively low.
[0204] The positive electrode active material of Example 3 is deficient in phosphorus and in the range of 3.7 < m < 4, and from Figure 12 it can be seen that the flatness of the small particles formed thereby is moderate, and the large particles formed by agglomeration thereof are relatively round, so that the tap density of the positive electrode active material layer formed thereby is relatively high.
[0205] The batteries provided by the positive electrode active materials of Example 2, Example 3 and Comparative Example 2 were subjected to rate performance tests, and the process was as follows:
[0206] Rate performance (5C capacity retention rate) test: the batteries were subjected to different rate discharge tests at room temperature 23℃, and the charge rate was uniformly 0.5C, and the discharge rate was 0.5C and 5C respectively. The discharge capacity retention rate of 5C rate compared with 0.5C rate was calculated, that is, the 5C capacity retention rate.
[0207] The results are shown in the following Table 2:
[0208] Example number Rate performance (5C capacity retention) Example 2 99.6% Example 3 99.8% Comparative Example 2 98.6%
[0209] From the above table, it can be seen that the positive electrode active material prepared by the method provided by the present application has good rate performance.
[0210] The above merely provides specific examples of the present application, and is not used to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall fall into the scope of protection of the present application.
Claims
1. A positive electrode sheet, characterized by, The positive electrode sheet includes a positive electrode active material layer including a positive electrode active material including Na x R y P m O n wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7 R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, In, Ga, Sn, Hf, Ta, W, and Pb.
2. The cathode electrode of claim 1, wherein, 3.8≤m<4。 3. The cathode sheet of any one of claims 1-2, wherein, The positive electrode active material has a chemical formula of Na x Fe y P m O n wherein 3.9≤x≤4.2, 2.8≤y≤3.1, 3.8≤m<4, 14.5≤n≤15.
5.
4. The cathode electrode of any one of claims 1-3, wherein, The relationship between the X-ray diffraction intensity I(602) of the (602) crystal plane of the positive electrode active material (602) and the X-ray diffraction intensity I(022) of the (022) crystal plane satisfies: I(602) / I(022) = 1.12-1.
15.
5. The cathode electrode of claim 4, wherein, The relationship between the X-ray diffraction intensity I(602) of the (602) crystal plane of the positive electrode active material (602) and the X-ray diffraction intensity I(022) of the (022) crystal plane satisfies: I(602) / I(022) = 1.13-1.
14.
6. The cathode sheet of any one of claims 1-5, wherein, The positive electrode active material has a porosity of 0.012 to 0.078 cm3 / g. 3 / g.
7. The cathode sheet of any one of claims 1-6, wherein, The positive active material has a chemical formula of Na x R y P m O n / C, wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7 R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, In, Ga, Sn, Hf, Ta, W, and Pb.
8. The cathode electrode of any one of claims 1-7, wherein, The positive electrode active material satisfies one or more of the following characteristics: (a) the first coulombic efficiency of the positive electrode active material is ≥ 93%; (b) the gram capacity of the positive electrode active material is 110-126 mAh / g; (c) the mass content of residual alkali in the positive electrode active material is ≤ 0.36%.
9. The cathode electrode of claim 8, wherein, The positive electrode active material satisfies one or more of the following characteristics: (a) the first coulombic efficiency of the positive electrode active material is ≥ 94%; (b) the gram capacity of the positive electrode active material is 123.2-125.8 mAh / g.
10. The cathode electrode of any one of claims 1-9, wherein, The compacted density of the positive electrode plate is 2.15-2.25 g / cm 3 .
11. A battery, characterized by The battery comprises the positive electrode sheet according to any one of claims 1-10.
12. A battery, characterized by The battery is a negative electrode-free battery comprising the positive electrode sheet according to any one of claims 1-10.
13. An electrical device, characterized by The power device comprises the battery according to claim 11 or 12.
14. A positive electrode active material, characterized in that The positive active material includes Na x R y P m O n wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7 R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, In, Ga, Sn, Hf, Ta, W, and Pb.
15. The positive electrode active material according to claim 14, characterized by The relationship between the X-ray diffraction intensity I(602) of the (602) crystal plane of the positive electrode active material (602) and the X-ray diffraction intensity I(022) of the (022) crystal plane satisfies: I(602) / I(022) = 1.12-1.
15.
16. A method for producing a positive electrode active material, characterized by, The method comprises: mixing a sodium source, an R source and a phosphorus source to obtain a mixture, the molar ratio of Na, R and P in the mixture being 3.5-4.7:2.3-3.5:3.5-4, wherein R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, In, Ga, Sn, Hf, Ta, W and Pb; sintering the mixture to obtain a positive electrode active material, the positive electrode active material comprising Na x R y P m O n wherein 3.5≤x≤4.5, 2.5≤y≤3.5, 3.7 14.5≤n≤15.
5.
17. The method of producing a positive electrode active material according to claim 16, characterized by, The mixture further comprises a carbon source.
18. The method of producing a positive electrode active material according to claim 17, characterized by, The carbon source comprises a first carbon source and a second carbon source, the first carbon source comprises an inorganic carbon source, and the second carbon source comprises an organic carbon source.
19. The method of producing a positive electrode active material according to claim 18, characterized by, The first carbon source comprises at least one of graphite, carbon black, carbon nanotubes and graphene; and / or The second carbon source comprises at least one of sucrose, glucose, citric acid, starch, cyclodextrin, pitch and PEG.